Penyalahgunaan Pemahaman Poligami dalam Pandangan Hukum Islam - Lintang Suci Nurliani,; Made Dian Kusuma Wardhani,; Kimilian Atrauzan Rosadi Anwar,; Rizky, Fauzi; Dico Raka Dewangga, (Moderasi: Jurnal Kajian Islam Kontemporer, 2023)
The practice of polygamy has existed since before Islam came and continues to survive with various cultural, social, economic and religious justifications. Polygamy itself has become part of the lifestyle of some men and because it is considered common by some perpetrators of polygamous practices, it makes the practice of polygamy a culture in a society or group. There is a shift in the meaning of polygamy, men who want more than one partner consider that polygamy is one of the worship in Islam, this refers to the Qur'an, tafsir, and related literature. This writing uses a qualitative research method of literature study, in which researchers collect various books and magazines that are relevant to the research objectives. In Indonesian society, polygamy is considered legal. However, people believe that polygamy allows women who are widows and orphans who need financial assistance to be able to polygamise with men who already have wives. In the Marriage Law No. 1 of 1974, in the context of polygamy whose legal subject is Muslim, the permissibility of polygamy is the absolute authority of the religious court. With the requirements and permits now Muslim men who want to do polygamy must ask permission from the Religious Court where he is located, as well as ensuring the fulfilment of needs by husbands who want to be polygamous, which is explained in several interpretations.